Atomic Platinum Anchored on Fe‐N‐C Material for High Performance Oxygen Reduction Reaction. Issue 2 (7th January 2020) - Sha, Ying; Ji, Jiapeng; Li, Siyuan; Gao, Xuehui; Zhang, Bingkai; Ling, Min; Liang, Chengdu; Lin, Zhan
Abstract : Development of highly active and stable catalysts to reduce the amount of Pt or replace Pt with nonprecious transition metal in acid of oxygen reduction reaction (ORR) is still an enormous challenge. Herein, we report anchoring atomic Pt particles on Fe/N‐doped carbon material (Pt1.1 FeNC) are, for the first time, synthesized by the photodeposition method. The obtained Pt1.1 FeNC electrocatalyst exhibits superior electrocatalytic activity and good stability for four‐electron oxygen reduction reaction (ORR) in an acidic electrolyte. Pt1.1 FeNC electrocatalyst shows a half‐wave potential of 0.85 V vs. reversible hydrogen electrode (RHE) in 0.1 m HClO4 (0.83 V of 20 wt.‐% commercial Pt/C). After 10, 000 cycles after, the catalysis active only decreases 20 mV. These are mainly due to the synergistic effect between Pt and Fe. Abstract : Photoreduction is used for the first time to prepare anchored Pt on Fe/N‐doped carbon materials to study the synergetic effect of Pt and Fe. The obtained Pt1.1 FeNC catalyst reduces the Pt mass loading while it improves the ORR catalytic activity.